A Study on negative impact of advertisement on children - Agarwal, Varsha (IJARIIT, 2022)
The purpose of this research is to make a review of the impact of television advertisements on children to understand the potential effect of TV advertising and specific pessimistic view of that exposure to young audiences. The study was conducted by using secondary data. Advertisement is a form of communication. It is about different products, services or ideas to its audiences. This paper deals with the analysis of negative impacts of advertisements on children which are telecasted on the television. In the present scenario TVs play an important role in our daily lives. The impact of advertisements on children is becoming catastrophic day by day. Findings indicated that television is not only providing entertainment, but also force young children to demand for must have items. Earlier, young children were off limits to advertisers and now they directly appeal to them. Advertisements create awareness among children in different aspects like entertainment, culture, news, sports and latest innovations & trends. In spite of this, all of these advertisements create a negative impact on children's minds. The adverse effects on children are interpreting and understanding the message being presented to them wrongfully. Aspects of the impact of TV advertising on children has spoiled their habitual actions, leading to pester, emerge conflicts and animosity in the family, increase the family budget, make demand for less nutritious products linked with obesity and poor health, imitate celebrities etc while it provides limited advantages.This paper deals with its negative effects and how to overcome those effects and provisional measures.
ISME
Keywords: Pessimistic View; Young Exposure; Adverse Effects; Miscommunication; Wrong Appeals; Television